Tigerland [videorecording (DVD)] - Schumacher, Joel, 1939-2020-; Farrell, Colin, 1976-; Davis, Matthew, 1978-; Collins, Clifton, Jr (20th Century Fox Home Entertainment, 2001)
Just released from the base stockade, recruit Roland Bozz joins a platoon of young soldiers preparing to ship out to Vietnam. His independence and outright defiance draw fire from his own men as well as commanding officers. But when the platoon is sent to Tigerland, a hellish training ground, Bozz's leadership and loyalty bring his men together, triggering extraordinary consequences.